Optimal Solar‐Biomass‐Diesel‐Generator Hybrid Energy for Water Pumping System Considering Demand Response - Olumuyiwa Taiwo Amusan; Nnamdi Ikechi Nwulu; Saheed Lekan Gbadamosi (Engineering Reports)
ABSTRACT The water pumping system is a vital daily operation for a sustainable society. The demand for this essential commodity is progressively growing around the world. Incorporating renewable energy sources (RES) into its operation mitigates adverse environmental effects stemming from greenhouse gas (GHG) emissions and reduces associated costs linked to fossil fuel energy sources. Hence, the optimal sizing of a hybrid mix of RES and non‐RES energy sources to power water pumping is essential. This study employs a generalized reduced gradient (GRG) optimization method to ascertain the most effective energy mix for water pumping system (WPS) application by integrating time of use demand response. This is achieved through four scenarios: Scenario 1 (S1) utilizes grid power and Diesel generator (DG) energy sources, Scenario 2 (S2) incorporates grid power, DG, and solar PV, Scenario 3 (S3) integrates grid power, DG, solar PV, and biomass energy sources, while Scenario 4 (S4) incorporates Time of Use (TOU) with the three aforementioned energy sources. The key findings reveal an ideal solution comprising of a mix of renewable PV and biomass along with non‐renewable grid energy source embedded with Time of Use demand response (S4) with optimal energy capacities of 4007 kW of PV, 4228 kW of grid, 234 kW of biomass, and 1085 of DG owing to the least cost energy and cost of water pumped of 0.75$/kW and 1.74$/kL, respectively, most volume of water pumped of 270.50 kL. These findings prove that the integration TOU demand response program with a hybrid mix of grid‐biomass‐DG‐solar PV is best suited for water pumping applications as it gives a cost‐competitive value.